Sex and race friendship preferences as expressed by preschool children - Şahinkaya, Rezan; Abel, Harold (The Turkish Journal of Pediatrics, 1961)
This study examined the sex and race friendship preferences expressed by preschool children. The sample consisted of 48 four-and five-year-old, white, upper-middle social class children attending the University of Nebraska Child Development Laboratory. Photographs of Negro and white boys and girls were used to develop two series of pictures, one for sex and one for race preference. Techniques were used to control for biasing factors, and a uniform statement was made to each subject at the beginning of the test session. T test revealed that sex preferences occur earlier than race preferences; boys and girls exhibit about the same degree of preference for their own sex, but there appears to be a strong trend for boys to favor their own race.